An Empirical Analysis of Director Turnover in US Banks During the Financial Crisis - Lu, Wenling; Whidbee, David A. (Journal of Accounting and Finance, 2024)
We examine the impact of bank risk-taking and performance on the director labor market outcomes of 3,263 bank directors associated with 279 publicly listed US banks during the financial crisis and subsequently. We find that risk-taking before the financial crisis increases the likelihood of turnover during the financial crisis for bank directors, particularly if the bank does not perform well relative to its peers. Consistent with the evidence for directors of non-financial firms, we find that directors of banks that performed relatively well during the financial crisis were less likely to experience turnover on the bank board. Surprisingly, the directors leaving the board before turning 70 years of age held fewer committee assignments, were less busy, had smaller networks, were less likely to be independent, and with larger banks and boards. Overall, we find evidence of bank performance influencing director turnover during and after the financial crisis.